Impact of Covid-19 on the digitalisation of administrative procedures - Kovač, Polonca (Teorija in praksa, 2021)
The Covid-19 pandemic has transformed our society, with administrative procedures - as relationships between public authorities and citizens and businesses - being no exception. Still, the innovative digitalisation of such procedures means the 58 administrative units across Slovenia have been able to develop a responsive administrative system. Using normative, descriptive and statistical research methods, the article identifies the relevant drivers and barriers, like user demands leading to a more responsive service, the lack of legal bases, and the top-down approach discouraging progress. Correlation analysis shows that digitalisation also holds important positive implications for the principles of good governance. Moreover, larger administrative units are more likely to achieve a higher degree of digitalisation and hence better public governance. The findings are useful for designing evidence-based public policies to properly respond to pandemic-associated challenges.
Keywords: administrative procedures; Covid-19; digitalisation; digitalizacija; dobro javno upravljanje; good public governance; innovation; inovativnost; javna uprava; public administration; Slovenia; Slovenija; upravni postopki